An Analysis of English Textbook for Fourth Grade Students of Bangladesh - Joy, Nafew Sajed (Universitas Nusantara PGRI Kediri, 2024)
This study critically examines the fourth-grade English textbook, English for Today, used in mainstream classrooms in Bangladesh. Despite 12 years of English instruction, many students in Bangladesh struggle with language proficiency, suggesting a gap between curriculum objectives and practical outcomes. The research investigates this gap by evaluating the textbook across four analytical stages. Initially, the study assesses the textbook’s aims, exercises, assessments, and learning process, identifying its intent to build language skills through engaging activities. The second step analyzes the textbook using various educational theories, such as social constructivism, Bloom’s taxonomy, the VARK model, and principles of pedagogy and educational psychology. These frameworks highlight the textbook’s attempt to foster active learning, critical thinking, and inclusivity. The third phase involves a critical evaluation of the textbook’s physical aspects, content quality, use of illustrations, and language structure. The research concludes with a content analysis, noting both strengths and weaknesses. The findings reveal that English for Today incorporates effective learning methods, such as hands-on activities and command-based instructions, aimed at enhancing student engagement. It demonstrates a strong alignment with educational theories, achieving a high readability score of 98.27. However, significant shortcomings are identified in the physical production of the textbook. Issues such as an unattractive cover, poor printing, and low-quality paper detract from the overall educational experience. Reflectively, the study underscores the importance of not just theoretical and content-based alignment in textbooks but also the material and visual aspects that affect students' motivation and engagement. While the textbook's pedagogical framework is sound, the findings suggest that improving its physical presentation could make it a more effective tool for language learning.